2020
DOI: 10.1177/1557988320949368
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Vasectomy Knowledge, Attitudes, and Information-Seeking Behaviors in the Southern United States: Results From an Exploratory Survey

Abstract: Vasectomy is one of the few options men have to manage their reproductive capacity and take on a more equitable role in pregnancy prevention. While the method is underused throughout the United States, the southern states have a lower prevalence rate compared to the rest of the country. Existing survey research does not assess what men know or think about the procedure as a means of understanding why this is the case. We created and conducted an exploratory survey to assess men’s knowledge, attitudes, and info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
(57 reference statements)
6
9
0
Order By: Relevance
“…Respondents demonstrated more accurate knowledge about not being able to get a sexual partner pregnant after undergoing vasectomy than about vasectomy’s effect on sexual functioning. These results are consistent with prior qualitative studies and recent survey findings of vasectomy knowledge in U.S. South ( Campbell et al, 2019 ; Shih et al, 2012 ; A. L. White et al, 2020 ). Erroneous perceptions about the impacts of vasectomy on sexual functioning may be related to men’s limited awareness about how vasectomy is performed and the biological processes involved in sexual functioning ( Campbell et al, 2019 ; Shih et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Respondents demonstrated more accurate knowledge about not being able to get a sexual partner pregnant after undergoing vasectomy than about vasectomy’s effect on sexual functioning. These results are consistent with prior qualitative studies and recent survey findings of vasectomy knowledge in U.S. South ( Campbell et al, 2019 ; Shih et al, 2012 ; A. L. White et al, 2020 ). Erroneous perceptions about the impacts of vasectomy on sexual functioning may be related to men’s limited awareness about how vasectomy is performed and the biological processes involved in sexual functioning ( Campbell et al, 2019 ; Shih et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Erroneous perceptions about the impacts of vasectomy on sexual functioning may be related to men’s limited awareness about how vasectomy is performed and the biological processes involved in sexual functioning ( Campbell et al, 2019 ; Shih et al, 2012 ). Like other studies ( Hubert et al, 2016 ; A. L. White et al, 2020 ), men in our sample who knew others who had a vasectomy were more knowledgeable about the procedure. Thus, these social connections may be able to dispel common myths and misinformation, even if men themselves do not have detailed knowledge of the procedure, and may reduce stigma surrounding vasectomy use ( Shih et al, 2012 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the study, the results of the respondents' poor knowledge were 82%, while the good respondents' knowledge was 18%. This research is supported by research conducted by White et al (2020) showed that poor respondent knowledge is more than good respondent knowledge. The respondents' poor knowledge is due to the fact that many people do not know about contraceptives for men other than condoms.…”
Section: Discussionsupporting
confidence: 62%
“…This bad respondent's knowledge is because the respondent never gets information and explanation about it. 8 Respondents' perceptions in this study were 75% had a negative perceptions while respondents with positive perceptions were only 15%. Research conducted by Shongwe et al (2019) supports this research with the results of the study being that the perception of respondents in the study who had a bad perspective was higher than a good perception.…”
Section: Discussionmentioning
confidence: 55%